Analysis of enteric ileal perforation: a prospective study in a tertiary care hospital - Shankar S., Prabu; P.B., Sudarshan; B.S., Sundaravadanan (International Surgery Journal, 2017)
Background: Intestinal perforation as a complication of enteric fever is still a serious problem in developing nations. Enteric ileal perforation is associated with high morbidity and mortality and many patients present in a severe toxic state because of delay in diagnosis and late presentation to hospital. Methods: A prospective study was conducted to assess the prognostic factors in enteric ileal perforation. Observations were made regarding symptoms, signs, duration of illness and presentation of patients to the hospital after acute episode. Per operative findings regarding site, size and number of perforations were recorded. Operative procedures were simple closure, ileostomy, or resection of diseased segment including right hemicolectomy done for associated caecal perforation and entero enteric anastomosis. Post-operative complications like wound infection, wound dehiscence, residual abscess, faecal fistula and deaths were documented. Results: There were 50 enteric ileal perforation cases with a age range of 13-80 with a mean age of 30.7. Male: female ratio was 11: 1. 85% of patients presented within 48 hrs of onset of symptoms of perforation and there is significant mortality in patients who presented more than 48 hrs of onset of symptoms of perforation (57.14%). Mortality was high in multiple perforation group (40%) and also higher incidences of fecal fistula and wound dehiscence. Conclusions: Age and sex have no bearing on the outcome. Perforation presentation interval, delay in surgery, number of perforations are important prognostic markers for typhoid ileal perforation.